2018
DOI: 10.1086/697447
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Sexual Selection on Ejaculate Traits under Sperm Competition

Abstract: The widespread prevalence of sperm competition means that ejaculates face intense sexual selection. However, prior investigations of sexual selection on gametes have been hampered by two difficulties: (1) deriving estimates of relative fitness from sperm competition trials that are comparable across rival male and female genotypes and (2) obtaining measures of competitive fertilization success that are not confounded by postzygotic effects. Here, we exploit the experimental tractability of a broadcast spawning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 75 publications
5
48
1
Order By: Relevance
“…overall sperm size; Humphries et al, ). Our findings also add to a growing number of studies that support this prediction (Fitzpatrick, Simmons, & Evans, ; Lymbery et al, ; Monro & Marshall, ). As such, measuring nonlinear selection on multivariate sets of sperm traits is likely to be a necessary (though sometimes complicated) step in assessing selection on sperm morphologies and predicting their adaptation to a changing world.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…overall sperm size; Humphries et al, ). Our findings also add to a growing number of studies that support this prediction (Fitzpatrick, Simmons, & Evans, ; Lymbery et al, ; Monro & Marshall, ). As such, measuring nonlinear selection on multivariate sets of sperm traits is likely to be a necessary (though sometimes complicated) step in assessing selection on sperm morphologies and predicting their adaptation to a changing world.…”
Section: Discussionsupporting
confidence: 84%
“…For males, fertility relies on the ability of sperm to collide and fuse with eggs; hence, selection has ample scope to target sperm traits that are involved in fertilization (Simmons & Fitzpatrick, ). Indeed, in a range of taxa, various aspects of sperm morphology play important roles in mediating sperm swimming performance (Lüpold, Calhim, Immler, & Birkhead, ; Malo et al, ), and ultimately male fertility (Lymbery, Kennington, & Evans, ; Monro & Marshall, ). For instance, sperm swimming speed is dictated by counteracting forces of thrust produced by the tail versus drag produced by the head and midpiece, which respectively house the nucleus and mitochondria (Humphries, Evans, & Simmons, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within a block, each individual male's fertilization success was assayed using pooled eggs from the same 4–6 females, thus minimizing the potential for male‐by‐female interaction effects in our measure of fertilization success (note that a different pool of females was used in each block). Previous work has confirmed that blocks of this size provide comparable estimates of fertilization ability among individual males across different pooled egg samples (Lymbery et al, 2018). Our total sample consisted of 23 blocks, comprising n = 138 males.…”
Section: Methodsmentioning
confidence: 56%
“…These observations of trait covariation suggest that ejaculate traits may be subject to both direct and indirect selection and correlational selection that favours particular combinations of traits, necessitating the use of multivariate analyses to separate components of selection (Blows, 2007; Lande & Arnold, 1983; Phillips & Arnold, 1989). A handful of recent studies have employed such approaches in external fertilizers and reported complex patterns of multivariate selection on sperm phenotypes (Fitzpatrick, Simmons, & Evans, 2012; Johnson, Monro, & Marshall, 2013; Lymbery, Kennington, & Evans, 2018). For example, using an experimental approach that manipulated the size of gametes at fertilization, Monro and Marshall (2016) reported that egg and ejaculate size independently mediate patterns of selection on sperm morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation